Question
upstudy study bank question image url

Select the inverse of each function. a. \( f(x)=-3 x-12 \) \[ \begin{array}{l}\text { A) } f^{-1}(x)=-3 x+36 \\ \text { B) } f^{-1}(x)=-\frac{1}{3} x-4 \\ \text { C) } f^{-1}(x)=-4 x-\frac{1}{3} \\ \text { D) } f^{-1}(x)=3 x+12\end{array} \] Part B b. \( g(x)=\frac{1}{3} x-12 \)

Ask by Patel Rose. in the United States
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The inverse of \( f(x) = -3x - 12 \) is \( f^{-1}(x) = -\frac{x + 12}{3} \), and the inverse of \( g(x) = \frac{1}{3}x - 12 \) is \( g^{-1}(x) = 3x + 36 \).

Solution

Function by following steps: - step0: Find the inverse: \(f\left(x\right)=-3x-12\) - step1: Replace \(f\left(x\right)\) with \(y:\) \(y=-3x-12\) - step2: Interchange the variables: \(x=-3y-12\) - step3: Swap the sides: \(-3y-12=x\) - step4: Move the constant to the right side: \(-3y=x+12\) - step5: Change the signs: \(3y=-x-12\) - step6: Divide both sides: \(\frac{3y}{3}=\frac{-x-12}{3}\) - step7: Divide the numbers: \(y=-\frac{x+12}{3}\) - step8: Replace \(y\) with \(f^{-1}\left(x\right):\) \(f^{-1}\left(x\right) = -\frac{x+12}{3}\) Find the inverse of the function \( g(x)=\frac{1}{3} x-12 \) Function by following steps: - step0: Find the inverse: \(g\left(x\right)=\frac{1}{3}x-12\) - step1: Replace \(g\left(x\right)\) with \(y:\) \(y=\frac{1}{3}x-12\) - step2: Interchange the variables: \(x=\frac{1}{3}y-12\) - step3: Swap the sides: \(\frac{1}{3}y-12=x\) - step4: Move the constant to the right side: \(\frac{1}{3}y=x+12\) - step5: Multiply by the reciprocal: \(\frac{1}{3}y\times 3=\left(x+12\right)\times 3\) - step6: Multiply: \(y=3x+36\) - step7: Replace \(y\) with \(g^{-1}\left(x\right):\) \(g^{-1}\left(x\right) = 3x+36\) Let's find the inverses of the given functions step by step. ### Part A: Finding the Inverse of \( f(x) = -3x - 12 \) 1. **Set the function equal to \( y \)**: \[ y = -3x - 12 \] 2. **Swap \( x \) and \( y \)**: \[ x = -3y - 12 \] 3. **Solve for \( y \)**: \[ x + 12 = -3y \] \[ y = -\frac{x + 12}{3} \] Thus, the inverse function is: \[ f^{-1}(x) = -\frac{x + 12}{3} \] Now, let's check the options provided: - A) \( f^{-1}(x) = -3x + 36 \) - B) \( f^{-1}(x) = -\frac{1}{3}x - 4 \) - C) \( f^{-1}(x) = -4x - \frac{1}{3} \) - D) \( f^{-1}(x) = 3x + 12 \) None of the options match the calculated inverse \( f^{-1}(x) = -\frac{x + 12}{3} \). ### Part B: Finding the Inverse of \( g(x) = \frac{1}{3}x - 12 \) 1. **Set the function equal to \( y \)**: \[ y = \frac{1}{3}x - 12 \] 2. **Swap \( x \) and \( y \)**: \[ x = \frac{1}{3}y - 12 \] 3. **Solve for \( y \)**: \[ x + 12 = \frac{1}{3}y \] \[ y = 3(x + 12) \] \[ y = 3x + 36 \] Thus, the inverse function is: \[ g^{-1}(x) = 3x + 36 \] In summary: - The inverse of \( f(x) = -3x - 12 \) is \( f^{-1}(x) = -\frac{x + 12}{3} \) (not listed in the options). - The inverse of \( g(x) = \frac{1}{3}x - 12 \) is \( g^{-1}(x) = 3x + 36 \).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To find the inverse of the function \( f(x) = -3x - 12 \), start by switching \( x \) and \( y \), giving you \( x = -3y - 12 \). Rearranging this equation to solve for \( y \) leads to \( y = -\frac{1}{3}x - 4 \). So, the correct inverse is option B) \( f^{-1}(x) = -\frac{1}{3}x - 4 \). For the function \( g(x) = \frac{1}{3}x - 12 \), we again switch \( x \) and \( y \) to obtain \( x = \frac{1}{3}y - 12 \). Rearranging to isolate \( y \) gives us \( y = 3x + 36 \). Thus, the inverse function is \( g^{-1}(x) = 3x + 36 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy